Cultural Phylogenetics Concepts and Applications in Archaeology - Mendoza Straffon, Larissa (Interdisciplinary Evolution Research, 2016)
This book explores the potential and challenges of implementing evolutionary phylogenetic methods in archaeological research, by discussing key concepts and presenting concrete applications of these approaches. The volume is divided into two parts: The first covers the theoretical and conceptual implications of using evolution-based models in the sociocultural domain, illustrates the sorts of questions that these methods can help answer, and invites the reader to reflect on the opportunities and limitations of these perspectives. The second part comprises case studies that address relevant empirical issues, such as inferring patterns and rates of cultural transmission, detecting selective pressures in cultural evolution, and explaining the nature of cultural variation. This book will appeal to archaeologists interested in applying evolutionary thinking and inferential methods to their field, and to anyone interested in cultural evolution studies.